Cursed by local institutions? An analysis of the role of institutions in the effects of natural resource abundance on the provision of public goods: evidence from peruvian municipalities - Contreras Medrano, Evelyn Edith (2016)
After decades of research, there is still no consensus in the literature regarding the effects of natural resource abundance on the economic and political performance of a territory. This research aims to contribute to this discussion, by analyzing the role of institutions on explaining the relationship between natural resource-based revenues and the provision of public goods at the local level. In order to do so, I test the mechanisms previously proposed in the literature for explaining the natural resource curse effect at the national level (mediation and moderation effects of institutional quality), using cross-sectional data of Peruvian municipalities located in the Andean highlands, for the 2011-2014 period. The identification strategy proposed uses as source of exogenous variation for revenues, the location of natural resources and its value among the territory, and a set of rules established by law for the redistribution of natural resource-based revenues to the local governments. In order to deal with the endogeneity of institutional quality, I include 2SLS estimations, using the presence of 'Peasant Communities' (Comunidades Campesinas) as an instrumental variable. The results show some evidence of a positive effect of natural resource-based revenues on the provision of local public infrastructure (water, public lightning and rural roads), a null effect on education results, and a negative effect on health campaigns. However, regarding the role of institutional quality on explaining these effects, I find no significant effects for all of the outcomes and samples analyzed.